New emission deterioration rates for gasoline cars – Results from long-term measurements. (January 2015) - Borken-Kleefeld, Jens; Chen, Yuche
Abstract: Vehicle emission control systems have been found to degrade with use resulting in increasing emission rates with vehicle age. Standard European data for deterioration factors have only been based on a sample of vehicles with limited high mileage ranges, with only few Euro 3 and Euro 4 vehicles, and on laboratory tests only. Here we present deterioration rates derived from more than 110′000 records collected over the past thirteen years from on-road emission remote sensing in Zurich/Switzerland. Deterioration rates for hot NOx and CO emissions of older gasoline vehicles are much lower than assumed so far, but significantly higher for Euro 3 and Euro 4 cars. There is no evidence of high emitters but equipment gradually degrades across the fleet. Deterioration rates do not seem to depend on engine load. Routine idle emission tests have not resulted in measurable emission reductions of the inspected vehicles. National emission inventories should be updated in the light of this new data. Highlights: On-road measurements over 13 consecutive years in Zurich/CH. Lower deterioration rates for Euro 1 and 2 cars, but higher deterioration for Euro 3 and 4 than assumed so far. No evidence for high emitters. No evidence for effectiveness of idle emission inspection tests.